Layer-by-layer (LbL) assembly of polyelectrolytes at the surface of a fiberglass membrane used as a support of the polarized liquid–liquid interface. (10th December 2020) - Borgul, Paulina; Rudnicki, Konrad; Chu, Liangyong; Leniart, Andrzej; Skrzypek, Sławomira; Sudhölter, Ernst J.R.; Poltorak, Lukasz
Highlights: The behavior of three polyelectrolytes (PEI, PSS and PHMG) is studied at the ITIES. Fiber glass membrane is modified with polyelectrolyte multilayer using LbL assembly. Unmodified fiber glass membrane is used as a support of the ITIES. Polyelectrolyte modified fiber glass membrane affect the ionic transport. Abstract: In this work, the electrified liquid–liquid interface (LLI) was supported with the bare and polyelectrolyte modified fiberglass membranes. The permeability of these supports was then investigated with ion transfer voltammetry (ITV). This work descends from three mutually interconnected experimental tasks. (i) The study of an interfacial behavior of three polyelectrolytes, poly(ethyleneimine) (PEI), polystyrene sulfonate (PSS), and polyhexamethylene guanidine (PHMG) at the polarized LLI. (ii) Electrochemical characterization of the LLI supported by the unmodified fiberglass membrane. (iii) Polyelectrolyte multilayer placement, using layer-by-layer processing, at the surface of the fiberglass membrane and its further utilization as the support for the electrified LLI. Bare and modified membranes were characterized using ITV in the presence of a family of quaternary ammonium cations: tetramethylammonium (TMA + ), tetraethylammonium (TEA + ), tetrapropylammonium (TPrA + ) and tetrabutylammonium (TBA + ) initially dissolved in the aqueous phase as the chloride salts. The ionic currents related to their transmembrane transfer were affected already after the first polyelectrolyte layer placement. In addition to electrochemistry, the modification process was followed using several complementary techniques, including optical microscopy (OM), atomic force microscopy (AFM), infra-red (IR) spectroscopy, and scanning electron microscopy (SEM). The proposed methodology offers very simple, fast, and versatile (having in mind the available selection of functional polyelectrolytes) protocol for a membrane preparation having size sieving properties. In turn, the electrochemistry at the LLI can be used as an insightful tool to study the ionic transmembrane currents. Graphical abstract: Image, graphical abstract